Q-switched erbium-doped fibre laser via sub-micron nickel particles saturable absorber - Mohd Yusoff, Norita; Che Aziz, Siti Asma; Husseini Zainol Abidin, Nadiah; Mahdi, Mohd Adzir; Alresheedi, Mohammed Thamer; Ng, Eng Khoon (Academic Press Inc., 2025)
We demonstrate a sandwich-type saturable absorber (SA) configuration of sub-micron nickel (Ni) particles aimed at generating Q-switched pulses in an erbium-doped fibre laser. The Ni-SA was fabricated by depositing the Ni materials in between two fibre ferrules with 2.38% modulation depth and 225 MW/cm2 saturation intensity. The integration of the Ni-SA in a ring cavity laser generated Q-switched pulses at around 1559 nm lasing wavelength. The pulse operation regime was obtained within 70–250 mW pump power, in which the pulse width and repetition rate were tuneable from 13.98 to 5.12 µs and 25.74 to 55.72 kHz, respectively. Meanwhile, the maximum achievable output power and pulse energy at 250 mW were up to 5.55 mW and 99.71 nJ, respectively. This work unlocks new possibilities of generating high energy microsecond pulses for valuable applications in the near future.